Significantly Improvement of Comprehensive Energy Storage Performances with Lead-free Relaxor Ferroelectric Ceramics for High-temperature Capacitors Applications. (15th January 2021) - Ye, Haoran; Yang, Fan; Pan, Zhongbin; Hu, Di; Lv, Xujiao; Chen, Hanxi; Wang, Feifei; Wang, Jiasheng; Li, Peng; Chen, Jianwen; Liu, Jinjun; Zhai, Jiwei
Abstract: Next-generation advanced electronic markets demand high energy-storage properties dielectric materials that can operate efficiently under elevated temperatures. Here, the Sr0.85 Bi0.1 TiO3 modified Bi0.4465 Na0.4465 Ba0.057 La0.05 TiO3 ceramics ((1-x)BNBLT-xSBT) are designed to achieve excellent comprehensive energy storage performances. The phase field simulations and experimental results indicate that the SBT doping into BNBLT ceramics could effectively decrease grain size, resulting in enhancement breakdown strength. Consequently, excellent comprehensive performances via a superior balance between recoverable energy density ( Wrec ~ 4.55 J/cm 3 ) and efficiency ( η > 90%) values have been realized in x=0.25 compositions. The corresponding ceramics exhibit impressive temperature stability (20~200 °C), fatigue endurance (10 5 st), and frequency stability (1~1000 Hz). More importantly, the BNBLT-0.25SBT ceramic shows a high power density (38.1 MW/cm 3 ) and a record discharge rate (45 ns). Therefore, this work will provide a simple and effective method to develop a new category of dielectric capacitors with superior energy-storage performances over an extended temperature range. Graphical Abstract: Image, graphical abstract